2006
DOI: 10.3354/cr030201
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of urbanization on land-atmosphere carbon exchange within a metropolitan area in the USA

Abstract: Urbanization can cause changes in carbon fluxes, which, in turn, impacts atmospheric carbon dioxide (CO 2 ) concentrations and possibly global surface temperatures. Using the Atlanta, Georgia, region as a case study, this paper explores the impact of urban expansion from 1973 to 2002 on land -atmosphere carbon exchange. The major objectives were to estimate net ecosystem production (NEP) values for multiple land-cover classes and to link urbanization-induced changes in land-cover to changes in NEP and overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…It has been shown that urban land expansion has significant impacts on atmosphere (Keller et al, 1991;Molders, 1999), regional climate (Carlson and Arthur, 2000;Xie et al, 2007;Jones et al, 2008), soil quality (Islam and Weil, 2000;Cao et al, 2007), hydrology (Weber et al, 2001;Li et al, 2008;Zhang et al, 2008), and ecosystem (Diem et al, 2006;Xu et al, 2007). Therefore, analyzing the characteristics and spatio-temporal differences of urban land expansion has great significances for sustainable urban development.…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that urban land expansion has significant impacts on atmosphere (Keller et al, 1991;Molders, 1999), regional climate (Carlson and Arthur, 2000;Xie et al, 2007;Jones et al, 2008), soil quality (Islam and Weil, 2000;Cao et al, 2007), hydrology (Weber et al, 2001;Li et al, 2008;Zhang et al, 2008), and ecosystem (Diem et al, 2006;Xu et al, 2007). Therefore, analyzing the characteristics and spatio-temporal differences of urban land expansion has great significances for sustainable urban development.…”
Section: Introductionmentioning
confidence: 97%
“…In particular, during the summer, these trends show diurnal asymmetric warming rates, where nighttime minimum temperatures ( T min ) have warmed faster than daytime maximum values ( T max ), thus decreasing the daily temperature range. The observed asymmetric warming during the last three decades at California coastal sites has been variously attributed to changes in cloud cover [ Nemani et al ., ], sea surface temperatures (SSTs) [ Goodridge , ; Karl et al ., ], increased upwelling [ Bakun ; Snyder et al ., ; McGregor et al ., ], land use changes for urbanization (LCLU) [ Mintz , ; Zhang , ; Chase et al ., ; Pielke et al ., ], irrigation [ Christy et al ., ; Bonfils and Lobell , ], greenhouse gases [ Duffy et al ., ; Walters et al ., ; Cayan et al ., ; Cordero et al ., ], Pacific Decadal Oscillation (PDO) [ Douville , ; LaDochy et al ., , ; Clark , ], and/or urban heat islands (UHIs) [ LaDochy et al ., ; Dai et al ., ; Kalnay and Cai , ; Diem et al ., ]. Furthermore, warming rates in California differ across seasons with higher warming in late winter/early spring and lowest in summer for daily maximum temperatures ( T max ) [ Bonfils et al ., ; Lebassi et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…However, for explaining regional warming, many different causes are cited. Some studies have looked at the role of urbanization and land use changes in causing regional warming (Christy & Goodridge 1995, Dai et al 1999, Kalnay & Cai 2003, Bereket et al 2005, Diem et al 2006). Christy & Norris (2004) argue that irrigation and soil moisture are major contributors, while others favor changes in cloudiness as a principal contributor to regional temperature variability (Henderson-Sellers 1992, Dai et al 1999, Braganza et al 2004).…”
Section: Introductionmentioning
confidence: 99%